Epoxy structure reinforced foaming material with excellent heat-conducting property as well as preparation method and application of epoxy structure reinforced foaming material
By introducing bubble structure and thermal filler into epoxy resin composite materials, combining the separated phase structure of solid and liquid epoxy resin, the problems of low thermal conductivity and brittleness of epoxy resin are solved, and efficient thermal management and mechanical properties are achieved. Improvement meets the demand for efficient thermal management materials of modern technology.
Patent Information
- Application Number
- CN202411518903.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-10
AI Technical Summary
The application of epoxy resin in the fields of efficient thermal management and automotive cavity structure enhancement is limited by its low thermal conductivity, high brittleness and poor toughness. In addition, increasing filler content will lead to a decrease in mechanical properties and increase in density, which is difficult to meet the needs of modern technology. The demand for efficient thermal management materials.
By introducing bubble structures into the thermally conductive composite material, a separate phase structure of solid epoxy resin and liquid epoxy resin is adopted, and combined with thermal filler and foaming agent, an epoxy structure-enhanced foaming material with excellent thermal conductivity and mechanical properties is formed. The volume repulsion effect and the flexibility of silicone rubber are used to improve the thermal conductivity and mechanical properties of composite materials.
It is realized that lightweight, high thermal conductivity and good mechanical properties are obtained under low filler content, which significantly reduces the material density and improves the modulus and tensile properties of the composite material. The process is simple and the cost is low.
Smart Images

Figure CN119286194A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of materials, and in particular to an epoxy structure-reinforced foam material with excellent thermal conductivity, and a preparation method and application thereof. Background Art
[0002] With the development of electronic devices, miniaturization and high power density, thermal management issues have become increasingly important. Excessive operating temperature will not only reduce the performance of electronic components, but also shorten their service life and even cause equipment failure. Therefore, the development of materials with excellent thermal conductivity to effectively dissipate heat has become one of the current research hotspots in the field of materials science and engineering.
[0003] Epoxy resin is widely used in electronic packaging, coatings, adhesives and composite materials due to its excellent mechanical properties, electrical insulation and chemical corrosion resistance. It is currently the most widely used thermosetting resin. However, due to its highly cross-linked structure, the cured product also has disadvantages such as high brittleness, poor toughness, and low thermal conductivity (usually around 0.2W / (mK)), which limits its use in industrial fields that require efficient thermal management and automotive cavity structure reinforcement. Therefore, improving the thermal conductivity of epoxy resin and improving the brittleness and poor toughness of its cured product are of great significance to expanding its application range.
[0004] In order to improve the thermal conductivity of epoxy resin, researchers have tried to introduce various high thermal conductivity fillers into its matrix, such as alumina, boron nitride, graphite, carbon nanotubes and metal powder. These fillers often need to be added in higher amounts to form thermal conductive channels in the matrix, significantly improving the thermal conductivity of the composite material. However, simply increasing the filler content will lead to a decrease in the mechanical properties of the material and may increase the density of the material, which is not conducive to practical applications.
[0005] Therefore, it is very necessary to develop a new type of composite material with good thermal conductivity and mechanical properties to meet the needs of modern science and technology and industry for efficient thermal management materials and automotive cavity structure reinforcement materials. Summary of the invention
[0006] The purpose of the present invention is to provide an epoxy structure reinforced foam material with excellent thermal conductivity and a preparation method and application thereof. By introducing a bubble structure into a thermally conductive composite material, the density of the material can be significantly reduced while maintaining or improving its mechanical properties and functional characteristics. The obtained epoxy structure reinforced foam material has excellent thermal conductivity and mechanical properties.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] In a first aspect of the present invention, there is provided an epoxy structure reinforced foam material having excellent thermal conductivity, wherein the raw materials for preparing the epoxy structure reinforced foam material having excellent thermal conductivity include, by weight:
[0009]
[0010] The prefabricated semi-cured material A is prepared from the following components in parts by weight: 100 parts of solid epoxy resin, 15-20 parts of elastomer, 10-20 parts of first curing agent, 0.5-2 parts of first curing accelerator, 5-15 parts of reinforcing agent, and 0.5-5 parts of foaming agent.
[0011] Furthermore, the parts by weight may be weight units well known to those skilled in the art, such as grams, kilograms, kilos, tons, etc.
[0012] The solid epoxy resin refers to bisphenol A type solid epoxy resin such as E-20, E-14, E-12, E-06, etc., preferably E12 type epoxy resin.
[0013] The elastomeric material refers to nitrile rubber, silicone elastomer, polyacrylate elastomer, etc., and nitrile rubber is preferred.
[0014] The first curing agent and the second curing agent respectively include amine curing agents (such as polyamide 651, ethylenediamine, m-phenylenediamine, polyetheramine D230, 2-methylimidazole), etc., anhydride curing agents (such as tetrahydrophthalic anhydride, polysebacic anhydride, methylhexahydrophthalic anhydride), etc., latent curing agents (such as dicyandiamide, boron trifluoride-amine complex), etc., preferably latent curing agents, specifically dicyandiamide is the best.
[0015] The first curing accelerator and the second curing accelerator respectively include tertiary amine accelerators (such as 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine), substituted urea accelerators (such as N-p-chlorophenyl-N,N-(3,4-dichlorophenyl)-N,N'-dimethylurea), phenol accelerators (such as phenol, resorcinol, o-cresol), imidazole accelerators (such as imidazole, 2-methylimidazole), acetylacetonate metal salts (such as triacetylacetonato vanadium, triacetylacetonato iron), boron trifluoride complexes (such as boron trifluoride triethanolamine complexes), preferably imidazole accelerators, specifically the best is 2-methylimidazole.
[0016] The reinforcing agent is any one of glass fiber, calcium carbonate, talc, wollastonite, montmorillonite, bentonite, glass microspheres, magnesium carbonate, kaolin, nano calcium carbonate or a mixture thereof, preferably glass fiber, specifically, glass fiber refers to short chopped alkali-free glass fiber with a length of 2-3 mm.
[0017] The foaming agent refers to a chemical foaming agent. Preferably, the foaming agent is azodicarbonamide (foaming agent ADC), expanded microsphere foaming agent, sodium bicarbonate, N,N'-dinitrosopentamethylenetetramine (foaming agent DPT, also known as foaming agent H), 4,4'-oxybisbenzenesulfonylhydrazide (foaming agent OBSH), p-toluenesulfonic acid hydrazine (foaming agent TSH), p-toluenesulfonamidourea (foaming agent RA), urea and its derivatives (foaming agent BK), diisopropyl azodicarboxylate, benzenesulfonylhydrazide (foaming agent BSH), biuret, biuret, nitrourea, carbohydrazide, p-toluenesulfonylacetonehydrazone, nitroguanidine, ammonium bicarbonate, sodium dihydrogen phosphate, citric acid and its derivatives. Any one or more of the mixture.
[0018] The liquid epoxy resin refers to bisphenol A type liquid epoxy resin such as E-51, E-52, E-42, E-44, etc., preferably E51 type epoxy resin. The epoxy value of the epoxy resin ranges from 0.38 to 0.54 (100 g / g).
[0019] The abbreviation of the liquid silicone rubber is LSR, and specifically, the optimal dosage is 12 parts.
[0020] The thermal conductive filler is any one of aluminum oxide, magnesium oxide, zinc oxide, aluminum nitride, boron nitride, silicon carbide, etc.
[0021] In a second aspect of the present invention, a method for preparing the epoxy structure-reinforced foam material having excellent thermal conductivity is provided, the method comprising:
[0022] S1, mixing the solid epoxy resin, elastomer, first curing agent, first curing accelerator, reinforcing agent and foaming agent by weight, pre-curing at 80-90° C. for 15-40 min, and then crushing into particles to obtain prefabricated semi-cured material A;
[0023] S2. Mix the prefabricated semi-cured material A with liquid epoxy resin, liquid silicone rubber, thermal conductive filler, second curing agent and second curing accelerator in parts by weight, process into sheets, and cure and foam to obtain an epoxy-based thermal conductive composite material with an expansion separation structure.
[0024] In S1, the banburying conditions are: 70-90° C., 8-15 min;
[0025] In S1, the range of the remaining epoxy value after pre-curing is 0.05-0.11 (100 g / g);
[0026] In S2, the process conditions for processing into sheets are compression molding or injection molding by a plunger injection molding machine at 70-90°C;
[0027] In S2, the curing and foaming temperature range is 150-190°C.
[0028] In a third aspect of the present invention, there is provided a use of the epoxy structure-reinforced foaming material having excellent thermal conductivity in the preparation of thermally conductive products.
[0029] The present invention has the following advantages and beneficial effects:
[0030] 1. The epoxy structure reinforced foam material with excellent thermal conductivity of the present invention has synergistic effects among the components in the composite material: (1) Due to the volume exclusion effect generated by the separated phases, the thermal conductive filler can be selectively dispersed in the mixed phase of E-51 and liquid silicone rubber. Compared with the randomly dispersed thermal conductive filler, the thermal conductivity of the composite material is greatly improved. (2) The first preform A prepared by solid epoxy resin and elastomer material can be used as a new toughening agent to improve the modulus and tensile properties of the composite material. (3) The silicone rubber mixed in the liquid epoxy resin can improve the flexibility of the composite material.
[0031] 2. The preparation method of the epoxy structure reinforced foam material with excellent thermal conductivity provided by the present invention uses solid epoxy resin as the separation phase and liquid epoxy resin as the continuous phase, and cleverly constructs an isolation structure so that the thermal conductive filler is selectively dispersed in the continuous phase, and the composite material is foamed, so that the composite material has light weight, high thermal conductivity and good mechanical properties at a low filler content. The process is simple and reasonable, the operation is convenient, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings in the following description are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0033] Figure 1 Schematic diagram of the preparation of the composite material. DETAILED DESCRIPTION
[0034] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0035] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0036] The present application will be described in detail below with reference to embodiments and experimental data.
[0037] Example 1
[0038] (1) 100 parts of E-12 solid epoxy resin, 15 parts of nitrile rubber, 20 parts of dicyandiamide curing agent, 4 parts of 2-methylimidazole, 1 part of foaming agent OBSH, and 5 parts of glass fiber are added to an internal mixer and mixed uniformly at 70° C. After mixing uniformly, the mixture is pre-cured at 90° C. for 30 minutes. The residual epoxy value is measured by chemical titration method to be 0.1025 (100 g / g). The pre-cured material is then crushed into particles A on an open double-roll mill, and the particle size of A is 20 mesh.
[0039] (2) Add 80 parts of particles A prepared in step (1), 10 parts of E-51 epoxy resin, 10 parts of liquid silicone rubber, 10 parts of boron nitride, 5 parts of dicyandiamide, and 0.2 parts of 2-methylimidazole into a reaction kettle, stir and mix them evenly, take them out, and use a plunger injection molding machine to injection mold them into sheets, and then cure them at 160° C. for 30 minutes to foam them. The foaming ratio is 2.8 times, the shear strength of the foamed material is 4.2 MPa, and the thermal conductivity is 1.3 W / (m·K).
[0040] Example 2
[0041] (1) 100 parts of E-12 solid epoxy resin, 20 parts of nitrile rubber, 15 parts of dicyandiamide curing agent, 2 parts of 2-methylimidazole, 1 part of foaming agent ADC, 2 parts of zinc oxide, and 10 parts of glass microspheres (1250 mesh) were added to an internal mixer and mixed uniformly at 70° C. After mixing uniformly, the mixture was pre-cured at 90° C. for 30 minutes. The residual epoxy value was measured by chemical titration method to be 0.084 (100 g / g). The pre-cured material was then crushed into particles A on an open double-roll mill, and the particle size of A was 20 mesh.
[0042] (2) Add 80 parts of particles A prepared in step (1), 10 parts of E-51 epoxy resin, 10 parts of liquid silicone rubber, 20 parts of boron nitride, 8 parts of dicyandiamide, and 0.5 parts of 2-methylimidazole into a reaction kettle, stir and mix them evenly, then take them out, compression mold them, and then cure them at 160° C. for 30 minutes to foam them. The foaming ratio is 2.7 times, the shear strength of the foamed material is 3.1 MPa, and the thermal conductivity is 2.1 W / (m·K).
[0043] Example 3
[0044] The 1 part of blowing agent OBSH in step (1) of Example 1 was adjusted to 2 parts of blowing agent OBSH, the 10 parts of liquid silicone rubber in (2) was adjusted to 15 parts, the curing and foaming at 160°C for 30 minutes was adjusted to the curing and foaming at 170°C for 30 minutes, and the other operations remained unchanged. The foaming ratio was 3.0 times, the shear strength of the foamed material was 3.4 MPa, and the thermal conductivity was 1.1 W / (m·K).
[0045] Example 4
[0046] The 10 parts of boron nitride in step (2) of Example 1 were adjusted to 15 parts of boron nitride, and the other operations remained unchanged. The foaming ratio was 2.7 times, the shear strength of the foamed material was 4.1 MPa, and the thermal conductivity was 1.6 W / (m·K).
[0047] Example 5
[0048] The 15 parts of nitrile rubber in step (1) of Example 1 are adjusted to 20 parts of nitrile rubber, the 10 parts of boron nitride in (2) are adjusted to 20 parts of boron nitride, the curing and foaming at 160°C for 30 minutes are adjusted to the curing and foaming at 180°C for 20 minutes, and the other operations remain unchanged. The foaming ratio is 2.6 times, the shear strength of the foamed material is 3.8 MPa, and the thermal conductivity is 1.85 W / (m·K).
[0049] Comparative Example 1
[0050] Directly add 80 parts of E-51 epoxy resin, 20 parts of liquid silicone rubber, 10 parts of boron nitride, 1 part of foaming agent OBSH, 20 parts of dicyandiamide, and 0.4 parts of 2-methylimidazole into the reactor, stir and mix them evenly, take them out, use a plunger injection molding machine to inject them into sheets, and then cure them at 160°C for 30 minutes to obtain a foaming ratio of 2.5 times, a shear strength of 2.9MPa, and a thermal conductivity of 0.55W / (m·K).
[0051] Comparative Example 2
[0052] The 20 parts of liquid silicone rubber in Comparative Example 1 were adjusted to 15 parts of liquid silicone rubber, and the 10 parts of boron nitride were adjusted to 20 parts of boron nitride, and the other operations remained unchanged, resulting in a foaming ratio of 2.6 times, a shear strength of the foamed material of 2.7 MPa, and a thermal conductivity of 0.85 W / (m·K).
[0053] Experimental Example 1
[0054] Some performance tests were conducted on the composite materials obtained in the above examples 1-5 and comparative examples 1-2. The test methods and results are shown in Table 1. The volume expansion rate (%) was measured by using an X-120X density balance to measure the density before and after foaming. According to the formula Calculated. The tensile strength was tested with a universal tensile testing machine at a tensile rate of 5 mm / min. The shear strength was tested with a universal testing machine at a clamp speed of 100 mm / min. The thermal conductivity was measured using a laser thermal conductivity meter to measure its thermal diffusion coefficient (α) and specific heat capacity (Cp), and its thermal conductivity was calculated according to the formula κ = α × Cp × ρ.
[0055] Table 1
[0056]
[0057] From Table 1, we can see that
[0058] Compared with Comparative Examples 1 to 2, the volume expansion rate, tensile strength, shear strength and thermal conductivity of Examples 1 to 5 of the present invention are greatly improved.
[0059] In summary, the present invention can significantly reduce the density of the material by introducing a bubble structure into the thermally conductive composite material, while maintaining or improving its mechanical properties and functional characteristics. The obtained epoxy structure reinforced foam material has excellent thermal conductivity and mechanical properties.
[0060] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0061] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0062] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. An epoxy structure reinforced foam material with excellent thermal conductivity, characterized in that: The raw materials for preparing the epoxy structure-reinforced foaming material with excellent thermal conductivity include, by weight: The prefabricated semi-cured material A is prepared from the following components in parts by weight: 100 parts of solid epoxy resin, 15-20 parts of elastomer, 10-20 parts of first curing agent, 0.5-2 parts of first curing accelerator, 5-15 parts of reinforcing agent, and 0.5-5 parts of foaming agent.
2. The epoxy structure-reinforced foam material with excellent thermal conductivity according to claim 1, characterized in that: The elastomeric material includes at least one of nitrile rubber, silicone elastomer, and polyacrylate elastomer.
3. The epoxy structure-reinforced foam material with excellent thermal conductivity according to claim 1, characterized in that: The first curing agent and the second curing agent respectively include at least one of an amine curing agent, an acid anhydride curing agent, and a latent curing agent, wherein the amine curing agent includes at least one of polyamide 651, ethylenediamine, m-phenylenediamine, polyetheramine D230, and 2-methylimidazole, the acid anhydride curing agent includes at least one of tetrahydrophthalic anhydride, polysebacic anhydride, and methylhexahydrophthalic anhydride, and the latent curing agent includes at least one of dicyandiamide and boron trifluoride-amine complex.
4. The epoxy structure-reinforced foam material with excellent thermal conductivity according to claim 1, characterized in that: The first curing accelerator and the second curing agent include at least one of a tertiary amine accelerator, a substituted urea accelerator, a phenol accelerator, an imidazole accelerator, an acetylacetone metal salt, and a boron trifluoride complex.
5. The epoxy structure-reinforced foam material with excellent thermal conductivity according to claim 1, characterized in that: The reinforcing agent includes at least one of glass fiber, calcium carbonate, talc, wollastonite, montmorillonite, bentonite, glass microspheres, magnesium carbonate, kaolin, and nano calcium carbonate.
6. The epoxy structure-reinforced foam material with excellent thermal conductivity according to claim 1, characterized in that: The foaming agent comprises at least one of azodicarbonamide, an expanded microsphere foaming agent, sodium bicarbonate, N,N'-dinitrosopentamethylenetetramine, 4,4'-oxybisbenzenesulfonylhydrazide, p-toluenesulfonic acid hydrazine, p-toluenesulfonamidourea, urea and its derivatives, diisopropyl azodicarboxylate, benzenesulfonylhydrazide, biuret, biuret, nitrourea, carbohydrazide, p-toluenesulfonylacetonehydrazone, nitroguanidine, ammonium bicarbonate, sodium dihydrogen phosphate, citric acid and its derivatives.
7. The epoxy structure-reinforced foam material with excellent thermal conductivity according to claim 1, characterized in that: The thermally conductive filler includes at least one of aluminum oxide, magnesium oxide, zinc oxide, aluminum nitride, boron nitride, and silicon carbide.
8. A method for preparing the epoxy structure-reinforced foam material with excellent thermal conductivity according to any one of claims 1 to 7, characterized in that: The preparation method comprises: The solid epoxy resin, elastomer, first curing agent, first curing accelerator, reinforcing agent and foaming agent are mixed by weight, pre-cured at 80-90° C. for 15-40 minutes, and then crushed into particles to obtain prefabricated semi-cured material A; The prefabricated semi-cured material A is mixed with liquid epoxy resin, liquid silicone rubber, thermal conductive filler, second curing agent and second curing accelerator according to weight parts, and then processed into sheets and cured and foamed to obtain an epoxy-based thermal conductive composite material with an expansion separation structure.
9. The preparation method according to claim 8, characterized in that: The curing and foaming temperature range is 150-190°C.
10. Use of the epoxy structure-reinforced foam material with excellent thermal conductivity as claimed in any one of claims 1 to 7 in the preparation of thermal conductive products and automotive cavity partition structure-reinforced products.